2021
DOI: 10.1016/j.clnu.2021.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of dietary glycemic index, glycemic load and fiber intake before and during pregnancy for the risk of gestational diabetes mellitus and maternal glucose homeostasis

Abstract: Background & aims: To date, the prevalence of Gestational diabetes mellitus (GDM) in China was 17.5%. Given the substantial relevance of GDM for medium-and long-term health of both mother and offspring and the paucity of existing data on the link between maternal diet and glucose homeostasis during pregnancy in Asian population, additional studies are needed. To examine the relevance of dietary glycemic index (GI), glycemic load (GL) and fiber intake before and during pregnancy for the development of GDM and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Such misconceptions were reported in findings of previously conducted studies [ 20 , 32 ]. Avoidance or minimal intake of whole grains such as “kollo” (roasted wheat or legumes) affect fiber intake of pregnant mothers which could increase the risk of developing gestational diabetes mellitus [ 34 ]. Furthermore, avoidance of animal source foods such as egg by pregnant mothers could lead to poor weight gain during pregnancy, low birthweight, embryonic losses, intra-uterine growth restriction, and reduced postnatal growth due to a deficiency in specific amino acids that are important for cell metabolism and function [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such misconceptions were reported in findings of previously conducted studies [ 20 , 32 ]. Avoidance or minimal intake of whole grains such as “kollo” (roasted wheat or legumes) affect fiber intake of pregnant mothers which could increase the risk of developing gestational diabetes mellitus [ 34 ]. Furthermore, avoidance of animal source foods such as egg by pregnant mothers could lead to poor weight gain during pregnancy, low birthweight, embryonic losses, intra-uterine growth restriction, and reduced postnatal growth due to a deficiency in specific amino acids that are important for cell metabolism and function [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the study's method, we can only analyze the effects of diets of observed patients, but there was no intervention group for which added fiber could be examined. In the recently published study performed by Zhang et al, women with the highest fiber intake before pregnancy, in the first trimester or the second trimester, had an approximately 11%, 17%, or 18% lower risk for GDM, respectively (p for trend ≤ 0.03) [78].…”
Section: Fibermentioning
confidence: 95%
“…A meta-analysis of 20 studies researching the influence of vitamin D deficiency, including 16,515 patients, demonstrated that it could increase GDM risk by 45% (RR 1.45; 95% CI 1.15-1.83; p < 0.001). The analysis also emphasized cofactors that intensify the influence of vitamin D deficiency on GDM risk, such as age (>30; OR 1.47; 95% CI 1.12-1.92 p = 0.005) or patient origin (developed countries; OR 1.44 95% CI 1.09-1.90; p = 0.011) [78]. However, in the Cochrane review of vitamin D interventions including 15 studies, the benefits of using vitamin D in the prophylaxis of GDM were not demonstrated [83].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Our group conducted several trials and reported improved cardiometabolic risks in non-pregnant adults following dietary berry intervention, primarily as blueberries, strawberries, or cranberry juice [ 24 , 25 , 26 ]. In addition, soluble fiber which is an essential component of berries and shown to be beneficial in diabetes [ 27 , 28 ] is not consumed at adequate levels by pregnant women [ 29 ]. Keeping in view the lack of such studies in pregnant women with obesity and cardiometabolic risks, we performed a clinical trial to examine effects following dietary blueberry and soluble fiber supplementation vs. standard prenatal care as control.…”
Section: Introductionmentioning
confidence: 99%